PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MEDIA TABEL DENGAN POWER POINT PADA SISWA SEKOLAH DASAR - Retno Sapartien (Universitas Muria Kudus, 2017)
The purpose of this study was to determine the effectiveness of the use of media "Table" with Power Point in mathematics learning material determine the greatest common factor and least common multiple in improving learning outcomes of learners and to determine changes in learning behavior. Using the method of action research consisted of two cycles and each cycle to follow the stages of planning, implementation of the action, observations, and reflection with data collection using observation, testing, and documentation. The results of the study in cycle 1 the average value of 76 students, with 19 students completed and there are 6 learners unfinished. While on the second cycle of the average value increased to 88 to 22 students completed and 3 learners still unresolved. Utilization of media tables in love with the variation application PowerPoint more effectively to instill the concept of how to determine the FPB and the Commission in learning mathematics in fourth grade elementary school Bonangrejo first half of the school year 2015/2016.